Analisis Kebutuhan Frekuensi Kapal Ro-Ro Dalam Melayani Penyeberangan - Muhammad Yazid; Husni Mubarak; Hari Hamid (Musamus Journal of Civil Engineering, 2023)
Air Putih - Sei Selari crossing of Bengkalis regency has a distance of 5 miles. The total number of Ro-Ro vessels operating at the parallel crossing of Air Putih – Sei Selari is 6 vessels with a rolling system where 4 vessels operate and 2 vessels are off / standby. The number of trips served per day is an average of 20 trips. However, the overall number of ships operating on a fairly close trajectory is not balanced with optimal ship operating time service. As a result there is a queue of ships to dock. In this study used several methods of analysis to solve the problems that occur, including load factor analysis, frequency analysis required and analysis of the needs of the number of ships. From the results of the analysis it was found that the ideal number of ship frequencies under normal and congested conditions were 21 trips/day and 24 trips/day respectively. Scheduling is based on ship service time during normal and busy times, both of that condition have Sailing Time 35 minutes, headways 90 minutes at normal condition and 103 minutes at congested, Layover time 20 minutes at normal times and 25 minutes at congested, so as to minimize the length of waiting time for ships to dock on the wharf. With a total of 6 ships, the ship operating schedule per day uses a ship rolling system with the division of 3 ships in operation and 3 ships off / standby.